A Comparison of Four Frailty Models - Malmstrom, Theodore K.; Miller, Douglas K.; Morley, John E. (Journal of the American Geriatrics Society (JAGS), 2014)
Objectives To determine how well the interview‐based, clinic‐friendly International Academy of Nutrition and Aging (FRAIL) frailty scale predicts future disability and mortality in the African American Health (AAH) cohort compared with the clinic‐friendly Study of Osteoporotic Fractures (SOF) frailty scale, the phenotype‐based Cardiovascular Health Study (CHS) frailty scale, and the comprehensive Frailty Index (FI). Design Longitudinal cohort study. Setting Metropolitan St. Louis, Missouri. Participants African American Health is a population‐based panel study of African Americans (baseline age 49–65) from St. Louis, Missouri. Participants completed in‐home assessments at baseline (N = 998) and 3‐ (n = 853) and 9‐ (n = 582) year follow‐up. Measurements Outcomes included activity of daily living (ADL) and instrumental ADL difficulties at 3 and 9 years and 9‐year mortality. Frailty measures included the FRAIL, SOF, and CHS scales and the FI. Results The FRAIL, SOF, CHS, and FI measures predicted new 3‐ and 9‐year disability, and the FRAIL and FI scales predicted 9‐year mortality. Receiver operating characteristic (ROC) contrasts showed that the FRAIL scale performed as well as (9‐year disability and mortality) or better than (3‐year disability) the CHS and SOF scales and the FI better than the FRAIL, CHS, and SOF scales for all outcomes except the FRAIL and CHS scales for 9‐year ADL difficulties. The CHS and SOF scales were equivalent for all outcomes in ROC contrasts. Conclusion Overall the FI and the FRAIL scale exhibited the strongest predictive validity for disability and mortality in AAH. The best prediction tool to identify frail individuals at risk of disability and mortality may be one that includes a comorbidity measure. The FRAIL scale includes a comorbidity item and is a brief interview‐based measure that is easy to administer, score, and interpret. The FRAIL scale has demonstrated validity and may prove to be a valuable scale for use by clinicians.